Hasil Penilaian Afektif Siswa Kelas VIII SMP dengan Menggunakan Model Pembelajaran Inkuiri Terbimbing (Jurnal Bioconcetta, 2017)
The objective of this research is to know the application of guided inquiry learning model to the biology learning result of the students of second years of yunior high school in the affective domain. The study was conducted in the odd semester of the academic year 2017/2018. The research is an experimental research using randomized control group postest only design research design. The study used two sample classes: the experimental class with given the application of Inquiry guided learning model and the control class using conventional learning method. The research instrument used is observation sheet of attitude evaluation. Indicators assessed are responsibility and confidence. The result showed that the average affective value of the experimental class is 82,50 (Good predicate) and the control class average is 73,85 (Good predicate). Working hypothesis accepted because tcount = 3.26> ttable = 1.672, and there are differences in student learning outcomes in both classes of samples significantly. That is means the implementation of Inquiry Learning model can improve the learning outcomes of biology of grade VIII SMP students affective